2011
DOI: 10.1164/rccm.201010-1706oc
|View full text |Cite|
|
Sign up to set email alerts
|

The Response of Children with Asthma to Ambient Particulate Is Modified by Tobacco Smoke Exposure

Abstract: Rationale: Ambient particulate matter concentrations have been positively associated with urinary leukotriene E 4 (LTE 4 ) levels and albuterol usage in children with asthma but interactions with environmental tobacco smoke (ETS) exposure have not been demonstrated despite obvious exposure to both pollutants in an urban setting. Objectives: To assess the health effects of concurrent ETS and ambient particulate matter exposure in children with asthma. Methods: Albuterol usage and LTE 4 levels were monitored in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
39
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 48 publications
4
39
1
Order By: Relevance
“…This observation is in agreement with previous studies reporting larger lung function decrement and more respiratory symptoms in response to ozone challenge in nonsmokers compared to smokers [35,36], which has been suggested to be explained by upregulation of antioxidant mediators in smokers [37,38]. Consistently, it has been reported that inflammatory response to air pollution in asthmatic children is more evident in those not exposed to environmental tobacco smoke (ETS) compared to those exposed to ETS [38]. Air pollution and ETS have been suggested to act as competing risk factors and saturation of common biological pathways of the effects of air pollution and ETS in those exposed to ETS has been proposed as a potential explanation for these findings [39].…”
Section: Discussionsupporting
confidence: 93%
“…This observation is in agreement with previous studies reporting larger lung function decrement and more respiratory symptoms in response to ozone challenge in nonsmokers compared to smokers [35,36], which has been suggested to be explained by upregulation of antioxidant mediators in smokers [37,38]. Consistently, it has been reported that inflammatory response to air pollution in asthmatic children is more evident in those not exposed to environmental tobacco smoke (ETS) compared to those exposed to ETS [38]. Air pollution and ETS have been suggested to act as competing risk factors and saturation of common biological pathways of the effects of air pollution and ETS in those exposed to ETS has been proposed as a potential explanation for these findings [39].…”
Section: Discussionsupporting
confidence: 93%
“…Some evidence is available to support this expectation. 101,115 What is clear is that polymorphisms of genes ( GSTM1 , GSTP1 , and TNF ) that have been associated with susceptibility to adverse asthma outcomes from exposure to air pollutants have also been associated with increased risks from exposure to secondhand smoke. 116118 …”
Section: Risk Modifiersmentioning
confidence: 99%
“…Several studies showed that especially fetal and infantile exposure to tobacco smoke increased the risk of asthma symptoms and lower respiratory tract infection in early childhood 59,60. ETS exposure also increases the vulnerability of the lungs to other air pollutants such as PM 61. Additionally, a recent study showed that prenatal exposure to cockroach allergen increased the risk of allergic sensitization in children at the age of 5-7 years and that exposure to nonvolatile polyaromatic hydrocarbons (PAHs) augmented the risk 62.…”
Section: Introductionmentioning
confidence: 99%